Pengaruh Citra Merek dan Kualitas Pelayanan Terhadap Keputusan Penggunana Jasa Angkutan Kapal Penumpang PELNI KM. Egon - Pricilya Maharani Amanda; Sudharto Prawoto Hadi (Jurnal Ilmu Administrasi Bisnis, 2017)
Purchasing decision is the goal which  every company has to achieve. KM. Egon PELNI must incorporate many factors which influence the purchasing decision. Moreover, the ship transportation is currently not priority for people.This purpose of this study is to determine the effect of brand image and service quality on purchase decision KM. Egon PELNI. This type of research is explanatory research. The sample used is 100 respondents. The sampling techniques is accidental sampling. The data collection techniques are questionnaire and literature review. Data analysis techniques are correlation, classic assumption, simple linear regression, multiple linear regression, t and f test with IBM SPSS (Statistical Product and Service Solutions) program version 19.0.Based on the analysis, it can be concluded that the brand image and service quality positively affects the purchase decision through testing simple linear regression produce regression value of 0.712 and 0.662. The advice  proposed to the company are to strengthen the brand image of product and to evaluate its service quality.